EFFECT OF FUEL TEMPERATURE ON SOME PERFORMANCE INDICATORS AND EXHAUST GAS EMISSIONS OF A FOUR CYLINDER DIESEL ENGINE - Haitham N. A; N. S. Kadhim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to evaluate the effect of diesel fuel temperature on engine performance and emissions. A 4-cylinder 4-stroke water cooled direct injection (DI) diesel engine was tested at three fuel temperatures (50, 60 and 70( °C. The fuel temperatures were controlled by A thermoelectric cooling system (TEC) fixed on the fuel supply line before the injection pump. The engine was run with two speed levels, included 1200 and 1500 rpm, with constant load (full load). An electric dynamometer was connected to the engine to make load by electric heaters. Gas emission was measured using gas analyzer type AirRex - HG540 and Texa gas box. Results obtained from the experiment were statistical analyzed using the factorial experiment system. The experiment design is (CRD), the averages of the results were tested using the least significant difference (LSD) at the probability level (0.05) using the (Genstat) program and showed that the fuel temperatures (50 °C) detected a sharp reduction in each of the brake specific fuel consumption (BSFC) by )6.95,4.34%) , Exhaust Gas Temperature(EGT) by (4.98,2.38%), Nitric Oxide (NOx) by )29.09,27.08%), and Particulate matter (PM) by (46.25,31.25%) and registered a slight increase brake thermal efficiency (BTE) of )7.12,4.40%) respectively, compared to the fuel temperature of (60,70) °C.